Why flipping the classroom is not enough: Digital curriculum making after the pandemic - Backes, Susanne (Prospects (Paris), 2021)
To slow down the proliferation of Covid-19, governments virtually shut down public life, temporarily closed schools, and forced teaching to be done exclusively on a remote basis. These measures offer an opportunity to reexamine conventional teaching and learning arrangements, test new digital and analogue concepts, and provide essential inspiration for curriculum making in the twenty-first century. This article addresses the historical development of schooling in the classroom as differentiated from “homeschooling”. On one hand, the question of how school closures and digitally supported teaching settings may affect an increase in educational inequalities is investigated using an international comparison. On the other hand, the pedagogical and didactical implications of distance learning and a digital teaching culture, which constitute the foundation for digital curriculum making, are examined.